The greatest store west of Chicago: Meier & Frank, 1857-1932. (20th February 2017) - Savitt, Ronald
Abstract : Purpose: The purpose of this paper was to document the development of a major regional department store from the firm's start to the completion of a single block structure including the warehouses required to support its operations. Design/methodology/approach: The study is based on a survey of historic materials including the recently available archival materials in the Oregon Historical Society Research Library. Findings: The study reveals the interaction of vision, planning and risk taking in a family enterprise over two generations. It illustrates the search for information as to what was required and the importance of architectural elements in the construction and operation of their store. Research limitations/implications: The archival materials are extensive; however, over the years, much of the operating data were destroyed or lost. Although family members remain in Oregon, they are reluctant to discuss the store's history, even though the matters that affected them took place many years after the study's period. Originality/value: Much of the information collected in the study had never been used in previous work.